New business models enabled by changes in international contracts and legislation between Finland and Russia - Lähdeaho, Oskari (2019)
The purpose of this thesis is to study new potential business models enabled by changed legislative and contractual environment between Finland and Russia. Most of these changes concern the freight traffic between these two countries, and in the bigger picture, between EU and CIS countries. In addition to the legislative and contractual changes, the effect of contemporary trends in business, innovations and technology to business models is studied. This study was conducted with qualitative approach, involving relevant companies and experts, both Finnish and Russian, for the premise of the thesis. The empirical research included 10 semi-structured interviews in Finland and Russia, and a survey that was distributed to manufacturing and logistics companies located in South Karelia. The carried out research resulted to three different business model archetypes, which are supported by the used theory as well as conducted empirical research: Business models based on blockchain and similar technologies enabling transparent communication within a cluster, platform based business models and business models based on innovative subcontracting in new sections of the product value chain. These business models exploit the changes in legislative environment, as well as emerging technologies and innovations. The presented models in this thesis are generalized to industry level and should be used as a reference to create specific company level business models that fit in the unique context of the given company, industry and type of business. Some of the companies that were involved in this thesis signaled interest towards experimenting and piloting the proposed business models. Through further refining these business models, as well as renewing the interested companies, the results of this thesis can be used to create new forms of business. Although the initial interest was from small and medium sized enterprises, as well as startup incubators, these models can also be used by larger and more incumbent companies to rethink their ...